Chemistry - McMurry, John; Fay, Robert C; Robinson, Jill K. (Always learning, 2016)
Make critical connections in chemistry clear and visible McMurry/Fay/Robinson's Chemistry, Seventh Edition, aims to help students understand the connections between topics in general chemistry and why they matter. The Seventh Edition provides a concise and streamlined narrative that blends the quantitative and visual aspects of chemistry, demonstrates the connections between topics, and illustrates the application of chemistry to their lives and careers. New content offers a better bridge between organic and biochemistry and general chemistry content, and new and improved pedagogical features make the text a true teaching tool rather than just a reference book.